2016
DOI: 10.1016/j.chom.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Perturbs Mitochondrial Morphodynamics to Dampen Innate Immune Responses

Abstract: With no antiviral drugs or widely available vaccines, Dengue virus (DENV) constitutes a public health concern. DENV replicates at ER-derived cytoplasmic structures that include substructures called convoluted membranes (CMs); however, the purpose of these membrane alterations remains unclear. We determine that DENV nonstructural protein (NS)4B, a promising drug target with unknown function, associates with mitochondrial proteins and alters mitochondria morphology to promote infection. During infection, NS4B in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
281
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(310 citation statements)
references
References 48 publications
23
281
0
6
Order By: Relevance
“…Two recent studies have investigated the role of mitochondria in DENV infection5455. In the first study Yu and colleagues showed that the DENV NS2B/NS3 protease cleaved two mitofusins which mediate mitochondrial fusion, resulting in disrupted mitochondrial membrane potential55.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have investigated the role of mitochondria in DENV infection5455. In the first study Yu and colleagues showed that the DENV NS2B/NS3 protease cleaved two mitofusins which mediate mitochondrial fusion, resulting in disrupted mitochondrial membrane potential55.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study Yu and colleagues showed that the DENV NS2B/NS3 protease cleaved two mitofusins which mediate mitochondrial fusion, resulting in disrupted mitochondrial membrane potential55. More recently Chatel-Chaix and colleagues showed altered mitochondrial morphology as a consequence of DENV NS4B protein interacting with mitochondrial proteins54. Importantly, Chatel-Chaix and colleagues showed elongation of mitochondria and increased contact with the DENV induced replication vesicles at the ER54, thus providing a mechanistic explanation for the increased colocalization between VDAC and GRP78 and L28 observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for the human cytomegalovirus exon 1 protein and viral mitochondrialocalized inhibitor of apoptosis (Bozidis et al 2010, Zhang et al 2011, for the hepatitis C virus core protein (Williamson & Colberg-Poley 2009, Horner et al 2011, 2015, for the human immunodeficiency virus protein-R (Huang et al 2012) and for the dengue virus (Chatel-Chaix et al 2016). The localization of some viral proteins at MAM was reported either to induce changes in the abundance of cellular proteins at MAM (Bozidis et al 2010, Zhang et al 2011 or to disrupt ER-mitochondria interactions in host cells (Huang et al 2012, Chatel-Chaix et al 2016 (Amr et al 2007). Interestingly, CISD2 was localized at MAM (Wang et al 2014), and adipocyte-specific loss of Cisd2 is associated with a reduction of ER-mitochondria interactions, mitochondrial dysfunction and altered insulin signaling in adipose tissue (Wang et al 2014).…”
Section: Er-mitochondria Miscommunication and Other Diseases Associatmentioning
confidence: 99%
“…DENV protease NS2b3 was shown to partially cleave Mfn1 and Mfn2 resulting in degradation of the proteins, which attenuated interferon responses and cell death [46]. A recent report was published while this manuscript was being prepared that showed that DENV NS4b induced mitochondrial elongation by inhibition of Drp1 activation and limited activation of the interferon response in a liver cell line [47]. Although these reports signify the importance of mitochondria and mitochondrial proteins during viral infection, the underlying mechanisms that link mitochondria and its proteins to DENV replication in target cell lines and primary cells has not been well studied.…”
Section: Introductionmentioning
confidence: 99%